The Contribution of Contemporary Interpretation in the Modern Era: A Study of the Concept of Thought and Methodology of Interpretation - Ahmad Ridho Syakiri (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
This paper aims to discuss the contribution of interpretation in the modern era which is examined through the concept of thought of the figures and the methodology of their interpretation. In this context, contemporary interpretation methods in the interpretation of the Koran make existing human problems the spirit of its interpretation. The research method used is library research, data presentation is descriptive, using historical-sociological analysis in the study of the science of the Qur'an. The results of this study are 1) the contribution of interpretation in the modern era has a lot of adab ijtima'i style so that it is very relevant to the human problems faced by humans in the current era; 2) the concept of thinking of contemporary figures is contextual by revealing the understanding of the meaning and values contained in the Qur'an to be actualized in overcoming contemporary problems and carrying out the moral ideals of the verses of the Qur'an such as the values of justice, equality, unity, and others not only interpret text literals only; 3) Contemporary interpretation methodology focuses more on thematic interpretation methods, emphasis on Arabic linguistics and language styles, double movement methods, and contextual interpretations